PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DENGAN GI (GROUP INVESTIGATION) PADA SISWA KELAS VIII SMP YP-PGRI 4 MAKASSAR - Johanis Pao Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Johanis Pao Ali. 2014. Comparison of Mathematics Learning Outcomes of Students Taught with TGT (Teams Games Tournament) Type Cooperative Learning Model with GI (Group Investigation) in Grade VIII SMP YP-PGRI 4 MAKASSAR. Thesis, Department of Mathematics Education, College of Teacher Training and Education (STKIP) Ujung Pandang Education Foundation (YPUP).This research is a type of experimental research carried out at SMP YP-PGRI 4 Makassar. This study aims to find out whether the mathematics learning outcomes of students taught with the TGT (Teams Games Tournament) type cooperative learning model are higher than the GI (Group investigation) type cooperative learning model. The research sample was grade VIIIA students of SMP YP-PGRI 4 Makassar consisting of 34 students who were taught using the TGT (Teams Games Tournament) type cooperative learning model and class VIIIB students consisting of 33 students using the GI (Group investigation) cooperative learning model, 2014/2015 school year. The data collection instrument used is a learning outcome test.The results of descriptive statistical analysis concluded that the learning outcomes taught used the TGT (Teams Games Tournament) type cooperative learning model with an average learning outcome score of 72.00 with a standard deviation of 12.30 while the learning outcomes taught using the GI (Group Investigation) type cooperative learning model) with an average learning outcome score of 61.42 with a standard deviation of 11.26. Based on the results of inferential statistical analysis, it can be concluded that the learning outcomes of squares and rectangles of students who are taught using the TGT (Teams Games Tournament) type cooperative learning model are higher than those of students who are taught using the GI (Games Investigation) type cooperative learning model.